Evolution,characteristics and revelation of the US cyber-security review system - Mengyuan ZHANG; Zhongyi YUAN (网络与信息安全学报, 2019)
As the founder of the global internet,the United States has established a well-structured cyber-security review system.It is based on a series of systematic and complete laws,regulations,and has constructed independent and efficient organizations.Such all-around and compulsory system is structured with distinctive characteristics,such as the extension and the procedure of the review in an orderly way,the vague standard and the compulsory results.Thus,it has certain reference significance to the establishment of a sound Chinese cyber-security review system.